Green and scalable synthesis of chiral aromatic alcohols through an efficient biocatalytic system. Issue 2 (31st May 2020) - Han, Meng‐Nan; Wang, Xu‐Ming; Pei, Chao‐Hong; Zhang, Chao; Xu, Zhidong; Zhang, Hong‐Lei; Li, Wei
Summary: Chiral aromatic alcohols have received much attention due to their widespread use in pharmaceutical industries. In the asymmetric synthesis processes, the excellent performance of alcohol dehydrogenase makes it a good choice for biocatalysts. In this study, a novel and robust medium‐chain alcohol dehydrogenase RhADH from Rhodococcus R6 was discovered and used to catalyse the asymmetric reduction of aromatic ketones to chiral aromatic alcohols. The reduction of 2‐hydroxyacetophenone (2‐HAP) to ( R )‐(‐)‐1‐phenyl‐1, 2‐ethanediol (( R )‐PED) was chosen as a template to evaluate its catalytic activity. A specific activity of 110 U mg −1 and a 99% purity of e.e . was achieved in the presence of NADH. An efficient bienzyme‐coupled catalytic system (RhADH and formate dehydrogenase, CpFDH) was established using a two‐phase strategy (dibutyl phthalate and buffer), which highly raised the tolerated substrate concentration (60 g l −1 ). Besides, a broad range of aromatic ketones were enantioselectively reduced to the corresponding chiral alcohols by this enzyme system with highly enantioselectivity. This system is of the potential to be applied at a commercial scale. Abstract : A novel and robust medium‐chain alcohol dehydrogenase RhADH from Rhodococcus R6 was discovered and used to catalyze the asymmetric reduction of aromatic ketones to chiral aromatic alcohols.